2001
DOI: 10.1364/josaa.18.002404
|View full text |Cite
|
Sign up to set email alerts
|

Perception of spatiotemporal random fractals: an extension of colorimetric methods to the study of dynamic texture

Abstract: Recent work establishes that static and dynamic natural images have fractal-like l/falpha spatiotemporal spectra. Artifical textures, with randomized phase spectra, and 1/falpha amplitude spectra are also used in studies of texture and noise perception. Influenced by colorimetric principles and motivated by the ubiquity of 1/falpha spatial and temporal image spectra, we treat the spatial and temporal frequency exponents as the dimensions characterizing a dynamic texture space, and we characterize two key attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…(iii) For all subjects, the noise contrast required for pattern formation dropped dramatically as the spatial exponent was increased from 0 to Ϸ1.0-1.4 (Fig. 5 a and c); these exponents are typical of the statistics of natural images (29). This effect is similar to that predicted by Busch et al (28) from simulations of spatiotemporal stochastic resonance in pattern-forming neural networks.…”
Section: Methodssupporting
confidence: 83%
“…(iii) For all subjects, the noise contrast required for pattern formation dropped dramatically as the spatial exponent was increased from 0 to Ϸ1.0-1.4 (Fig. 5 a and c); these exponents are typical of the statistics of natural images (29). This effect is similar to that predicted by Busch et al (28) from simulations of spatiotemporal stochastic resonance in pattern-forming neural networks.…”
Section: Methodssupporting
confidence: 83%
“…Neurons in early visual cortex (i.e., V1) process images by band-pass filtering, so their analysis of visual information can be considered to be optimally efficient (15, 16). Furthermore, it has been demonstrated that the correlational structure of adult human contrast sensitivity data displays a power law consistent with natural images (13,17).Behaviorally, discrimination of changes in amplitude spectrum is most accurate when ␣ is approximately 1.5 spatially (18)(19)(20)(21) and ␣ is between 0.8 and 1 temporally (21). Surround suppression is stronger with surrounds of natural amplitude spectra compared with less natural surrounds (22).…”
mentioning
confidence: 98%
“…Behaviorally, discrimination of changes in amplitude spectrum is most accurate when ␣ is approximately 1.5 spatially (18)(19)(20)(21) and ␣ is between 0.8 and 1 temporally (21). Surround suppression is stronger with surrounds of natural amplitude spectra compared with less natural surrounds (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the perceptual and emotional properties of static textures in general (eg, Machajdik and Hanbury 2010; Mao et al 2003), and the effects of their color distribution in particular (eg, Lucassen et al 2011; Simmons and Russell 2008), have been well documented. It appears that the human visual system is optimized for the perception of natural images (Field 1987, 1994; Parraga et al 2000), which typically have fractal-like spatiotemporal spectra (Billock 2000; Billock et al 2001a, 2001b). The amplitude spectra of dynamic natural textures closely follow an inverse power law relationship: A(fs,ft)=cfsβftα where f s and f t are, respectively, the spatial and temporal frequency, with 0.9 ≤ β ≤ 1.2 ( M = 1.08; Billock 2000), and 0.61 ≤ α ≤ 1.2 (Billock et al 2001b).…”
Section: Introductionmentioning
confidence: 99%